Medieval jewelry and burial assemblages in Croatia : a study of graves and grave goods, ca. 800 to ca. 1450 - Sokol, Vladimir, 1948- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2016)
The Croatian medieval archaeological heritage from the 8th to the 15th century consists mostly of jewelry (earrings) findings from cemeteries. This book uses vertical and horizontal stratigraphy, on the basis of around 20,000 burial assemblages from 16 cemeteries (out of several hundred so far excavated in Croatia), to establish relative and absolute chronology of jewelry and burial architecture divided into three horizons and four phases in comparison with materials from neighboring regions of Europe.